Isolation and identification of strawberry anthracnose and fungicide screening in Henan province - SUN Wenbin; ZHANG Jingjing; SONG Yanhong; ZHAO Xia; LI Gang; ZHOU Houcheng; LIU Lifeng (Guoshu xuebao)
[Objective] Strawberry anthracnose, caused by fungi of the genus Colletotrichum, presents a significant threat to strawberry cultivation in Henan Province, China. The rapid proliferation of this disease has led to considerable yield losses and a decline in fruit quality. The primary objective of this comprehensive study is to identify the species and predominant strains of pathogenic fungi associated with strawberry anthracnose. Additionally, the research aims to evaluate the efficacy, safety, and overall effectiveness of various fungicides in managing this disease. By identifying the most suitable fungicides, agricultural practitioners in Henan province can implement improved disease management strategies that enhance both sustainability and productivity within their strawberry farming operations. [Methods] To achieve the objectives outlined above, a systematic and multifaceted methodology was employed. This research specifically focused on strawberry anthracnose attributed to Colletotrichum. Initially, samples exhibiting symptoms of strawberry anthracnose were collected from three major strawberry cultivation regions in Henan province including Zhengzhou, Xinxiang, and Mengzhou. Tissue isolation technique was utilized to extract and purify pathogens from these samples, resulting in pure cultures of the pathogenic fungi. The primary biological characteristics of these isolates were examined with an emphasis on how various environmental factors, such as temperature, pH levels, carbon sources, and nitrogen sources, influenced mycelial growth. Inoculation experiments were conducted to determine the pathogenicity of isolated strains, which involved inoculating detached leaves, petioles, and fruits of strawberries as well as applying spore suspensions onto living strawberry leaf surfaces and integrating spore suspensions into substrates. The concentration of the spore suspension employed in these experiments was standardized at 1.0×105 spores·mL-1 to ensure consistency and reproducibility of results. Given the lack of effective agents specifically designed for controlling strawberry anthracnose in agricultural production, the mycelial growth rate method was utilized for indoor virulence testing and to evaluate the efficacy of ten selected fungicides. This approach enabled an assessment of the sensitivity of isolated strains to various fungicides, thereby providing valuable insights into potential agents that may be effective in managing this disease. [Results] The findings indicated that all the five isolated strains derived from strawberry anthracnose samples exhibiting characteristic symptoms from the specified regions were classified as Colletotrichum siamense. The conidia size was (15.95±1.06)μm by (4.49±0.38)μm. Among the five strains, designated ZG-2 to ZG-6, strain ZG-2 exhibited the highest level of pathogenicity. Inoculated leaves with strain ZG-2 displayed rot after one week, while the lesion areas caused by the other strains were less than 50%, indicating a lower pathogenicity in comparison to ZG-2. The C. siamense ZG-2 strain was found to be highly pathogenic to strawberry plants, affecting various plant parts including leaves, fruits, petioles, stem bases, and roots. The infectivity of strain ZG-2 varied across different plant components, petioles and stem bases experienced the most severe damage, followed by leaves, fruits, and roots. Notably, distinct orange spores were observed on detached leaves approximately seven days post-infection, leading to leaf rot. During live inoculation experiments, lesions on the abaxial surface of the leaves were larger and more numerous than those on the adaxial surface, indicating a higher susceptibility of the abaxial side to infection by this strain. Following root infection, plants exhibited inhibited growth characterized by a marked decrease in both leaf and root quantity as well as reduced root lengths, brown lesions appeared on root surfaces compared to controls. Specifically recorded measurements for root length (3.72 cm), fresh weight (0.452 g), and dry weight (0.082 g) reflected significant reductions of 40.7%, 43.7%, and 64.6% respectively when compared with healthy control groups. The occurrence of stem base rot could ultimately lead to mortality in strawberry plants. The biological characteristics of the ZG-2 strain were distinctly notable, as it demonstrated the ability to grow within a temperature range of 15℃to 35℃, with the most rapid mycelial growth rate of 6.2 mm per day observed at 27℃. The optimal pH for growth was determined to be 8, and the strain exhibited resilience across a pH range of 4 to 11, indicating strong adaptability to varying acid-base conditions. Soluble starch and peptone were identified as the most effective sources of carbon and nitrogen, respectively. The antibacterial efficacy of the ZG-2 strain was assessed with relative accuracy. Among the ten agents tested, propiconazole, cyproconazole, and benzoic-prochloraz displayed effective antibacterial properties, with EC50 values recorded at 0.035 μg·mL-1, 0.048 μg·mL-1, and 0.089 μg·mL-1, respectively. Tebuconazole at a concentration of 430 g·L-1 exhibited superior control against the pathogen. [Conclusion] Strawberry anthracnose has been documented in Henan Province, particularly in Zhengzhou, Xinxiang, and Mengzhou, throughout the entire growth cycle of strawberry plants. This disease results in significant blight and mortality rates that considerably hinder development of the strawberry industry in this region. To elucidate the primary pathogenic fungi affecting strawberries in the Henan Province, DNA was extracted from each isolated and purified fungal strain, subsequently, PCR amplification was performed using the ITS-1F/ITS-4R primers. The obtained sequences were analyzed via BLAST on the NCBI database, revealing strains with 99% similarity to known species. The results indicated that the predominant pathogenic fungal genera in this region include Colletotrichum, Fusarium, Botrytis, Cladosporium, Alternaria, Phytophthora, Pilidium, and Oomycetes. Notably, Colletotrichum, the causative agent of strawberry anthracnose, was identified as a common strain across the three representative regions. A total of fifty-two isolates of the pathogen were collected from strawberry samples in Henan Province. Through polygenic analysis coupled with associated infection studies, C4iamense ZG-2 was identified to be closely related to Anthracis siamensis. It exhibited a self-spreading rate of approximately 72%. Disease resistance evaluation were conducted on seven commercially cultivated strawberry varieties, as well as three advanced breeding lines (designated as zx.19.3, zx.60.11, and zx.32.17) selected by the research group. The results revealed that the fungal strain C. siamense ZG-2 exhibited pathogenicity across all tested strawberry varieties. Moreover, significant variations in resistance levels were observed among the different cultivars, each demonstrating distinct capacities to resist pathogen infection. This strain has been classified as a pathogenic species responsible for causing strawberry anthracnose in Henan Province. C. siamense is recognized as a major pathogen affecting various crops throughout China. The findings suggest that pentazolol demonstrates strong inhibitory effects on strawberry anthracnose and may serve as an effective agent for managing this disease.